Pengaruh Kepemimpinan Kepala Sekolah Terhadap Motivasi Kerja Guru Di Sekolah Menengah Atas Negeri 1 Angkola Timur - Pasaribu, Safran Efendi; Darwis, Darwis; Syaputra, Adi (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2023)
The research aims to see the influence of school principal leadership management on teacher work motivation. The research population was all teachers at East Angkola 1 State High School. The research uses quantitative methods and correlational research types. The research instrument used a questionnaire. The research results show that, first, the principal's leadership management has a good effect on teacher performance. Second, the motivation of the school principal has an influence on teacher performance. Third, work motivation influences teacher performance at SMA Negeri 1 Angkola Timur. Therefore, it can be concluded that the principal's leadership has a positive effect on teacher work motivation at East Angkola 1 State High School (SMA).